Analisis Tingkat Kepedulian Masyarakat terhadap Kebersihan Lingkungan di Kecamatan Pante Raja - Erna Safitri; Safitria Safitria; Mika Sari; Selly Hidayanti; Siti Aminah (Public Health Journal, 2026)
Environmental cleanliness is one of the essential determinants of community health. Community awareness plays an important role in maintaining environmental sanitation and reducing the risk of environment-related diseases. This study aimed to analyze the relationship between community awareness and environmental cleanliness in Pante Raja District, Pidie Jaya Regency, Aceh. An analytical quantitative study with a cross-sectional design was conducted involving 29 respondents selected using the total sampling technique. Primary data were collected through structured questionnaires and direct observations. Data were analyzed using descriptive statistics and the Chi-Square test with a significance level of 0.05. The results indicated that 51.7% of respondents had a low level of environmental awareness, while 69.0% of the observed environments were categorized as having poor cleanliness. Statistical analysis demonstrated a significant relationship between community awareness and environmental cleanliness (p<0.001). Respondents with higher awareness were more likely to maintain cleaner surroundings than those with lower awareness. These findings emphasize that strengthening community participation through environmental education, health promotion, and waste management programs is essential for improving environmental quality and preventing environmental health problems. This study provides empirical evidence that community awareness is an important factor in achieving sustainable environmental health at the community level.